Histopathology of the Black Plaice Pseudopleuronectes Obscurus from a Marine Reference Area - Iraida Germogenovna Syasina (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
The Kievka Bay is one of the cleanest regions on the Far East coast of Russia. There are no anthropogenic impacts on the coastal area, and thus the influence of pollutants on the state of fish health is minimized. Histopathological examination of black plaice was performed to study the background level of morbidity and the occurrence of pathological alterations in tissues of fi shes from this ecologically clean region. Different pathological alterations were detected in fi shes sampled. The most surprising was a disease of black plaice, where necrotic changes were found in the gonads of 28% of the males, and the destructive changes were absent in females. In the gills, pathogenic microorganisms were detected, which induced strong hyperplasia of the respiratory epithelium, fusion of lamellas, and necrosis of pillar cells, in 28% of the individuals. Diseases of the liver were recorded for two fishes that comprised 8% of the total number, in one case - granulomatous inflammation. Besides that some fishes had a diffuse necrosis in the liver. In the kidneys of all sampled fish, parasites were present in the lumen of the renal duct, very likely a moderately pathogenic species, as the consequences of parasitism were insignificant and for a smaller part of fishes - moderate. Thus, different pathological alterations were found in all investigated organs, and, in most cases, it was possible to establish their occurrence with parasitism.